2009
DOI: 10.1080/09638280902847085
|View full text |Cite
|
Sign up to set email alerts
|

First rehabilitation consultation in patients of non-native origin: Factors that lead to tension in the patient–physician interaction

Abstract: Sources of tension were identified during the interaction between Dutch physicians and patients of Turkish and Moroccan origin. These factors potentially are associated with future drop-out. Future research should clarify whether these factors indeed are associated with drop-out.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 15 publications
2
5
0
Order By: Relevance
“…Differences in the utilization and outcomes of rehabilitation between German and non-German nationals cannot be explained by differences in health status or demographic and socio-economic factors [ 11 , 13 – 15 ]. Similar results were reported from other countries [ 16 19 ]. For example, Sloots et al observed higher rates of drop-out from rehabilitation among Turkish and Moroccan migrants as compared to the Dutch majority population in the Netherlands [ 16 , 17 ].…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…Differences in the utilization and outcomes of rehabilitation between German and non-German nationals cannot be explained by differences in health status or demographic and socio-economic factors [ 11 , 13 – 15 ]. Similar results were reported from other countries [ 16 19 ]. For example, Sloots et al observed higher rates of drop-out from rehabilitation among Turkish and Moroccan migrants as compared to the Dutch majority population in the Netherlands [ 16 , 17 ].…”
Section: Introductionsupporting
confidence: 92%
“…Similar results were reported from other countries [ 16 19 ]. For example, Sloots et al observed higher rates of drop-out from rehabilitation among Turkish and Moroccan migrants as compared to the Dutch majority population in the Netherlands [ 16 , 17 ].…”
Section: Introductionsupporting
confidence: 92%
“…This is disturbing, as educational level (as an indicator of socioeconomic status) is inversely related to the duration and recurrence of back pain (Dionne et al, 2001); a stronger consideration of the demands of patients with low socioeconomic status might improve prognosis. Similarly, a stronger consideration of the cultural background of patients could help to change inappropriate beliefs about the origin and treatment of low back pain, generate more realistic expectations regarding rehabilitation and thereby enhance outcomes (Sloots et al, 2009). We also did not find any sex-specific recommendations referring to interventions tailored for women.…”
Section: Discussionmentioning
confidence: 53%
“…Two reviewers identified 492 potential concepts in 77 primary studies ( Figure 3). They excluded 115 potential concepts for the following reasons: inadequate conceptualisation (31 concepts in 17 studies 11,150,155,160,162,169,173,178,181,188,192,196,197,206,208,219 ); did not explore HCP experience (18 concepts in seven studies 168,174,198,202,203,215,223 ); and explored a topic with limited transferability beyond a specific context (five concepts in five studies 166,167,197,208,223 ). We agreed that for some topics there were insufficient concepts to allow us to develop robust conceptual categories: return to work (seven concepts in two studies 167,182 ), ethnicity (11 concepts in five studies 171,204,205,215,216 ), gender (seven concepts in one study 206 ) and older people (21 concepts in nine studies 159,160,162,165,176,187,194,199,…”
Section: Coding and Conceptual Categoriesmentioning
confidence: 99%
“…Relevance and aim of included studies (continued ) First author and year Relevance Study aim Slade 2012 214 Direct To investigate how physiotherapists prescribe exercise for people with non-specific chronic low-back pain in the absence of definitive or differential diagnoses a Sloots 2009215 Direct To explore which factors lead to tension in the patient-physician interaction in the first consultation by rehabilitation physicians of patients with chronic non-specific low-back pain who are of Turkish and Moroccan origin…”
mentioning
confidence: 99%